2021
DOI: 10.1007/978-3-030-89177-0_4
|View full text |Cite
|
Sign up to set email alerts
|

Deep Semantic Segmentation of 3D Plant Point Clouds

Abstract: Plant phenotyping is an essential step in the plant breeding cycle, necessary to ensure food safety for a growing world population. Standard procedures for evaluating three-dimensional plant morphology and extracting relevant phenotypic characteristics are slow, costly, and in need of automation. Previous work towards automatic semantic segmentation of plants relies on explicit prior knowledge about the species and sensor set-up, as well as manually tuned parameters. In this work, we propose to use a supervise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Heiwolt et al [301] applied the PointNet++ architecture, adjusted for point-wise segmentation applications, on tomato plants and showed that this network was able to successfully predict per-point semantic annotations for soil, leaves, and stems directly from point cloud data.…”
Section: Point-based Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heiwolt et al [301] applied the PointNet++ architecture, adjusted for point-wise segmentation applications, on tomato plants and showed that this network was able to successfully predict per-point semantic annotations for soil, leaves, and stems directly from point cloud data.…”
Section: Point-based Methodsmentioning
confidence: 99%
“…Deep Learning (DL) Banana [90] Maize (Corn) [160,299,310,313] Rice [311] Rosebush [264] Rosette plants [1] Sorghum [276] Thale cress (Arabidopsis) [17] Tobacco [276] Tomato [2,160,276,301] DL is a very commonly employed algorithm in the ML algorithms, and it is derived from the conventional neural network but considerably outperforms its predecessors. DL employs transformations and graph technologies simultaneously in order to build up multi-layer learning models.…”
Section: Machine Learning Techniquesmentioning
confidence: 99%
“…Segmentation of plants into organs is an essential step prior to the extraction of phenotypic traits. Deep learning methods such as PointNet++ variants have shown promise for this in the context of tomato plants, performing 3D semantic segmentation of synthetically generated plants without prior knowledge of species and sensor setup (Heiwolt et al., 2021). In comparison to cereal crops, such as wheat, both the complex growth habit of the strawberry plants, as well as their relatively small size, increase the phenotyping complexity (Zheng et al., 2021).…”
Section: Current Status Challenges and Prospects Of Automated Strawbe...mentioning
confidence: 99%
“…More recently, Chebrolu et al (2021) achieved leaf and stem segmentation using a support vector machine (SVM) based on fast point feature histograms (FPFH). However, these methods rely on human work to provide discriminative features for segmentation, a process which is sensitive to natural variations of plants even within a same cultivar, resulting in poor generalization (Heiwolt et al, 2021).…”
Section: Introductionmentioning
confidence: 99%